From 'no dogs here!' to 'beware of the dog!': restricting dog signs as a reflection of social norms. (November 2021) - Halonen, Mia; Laihonen, Petteri
Signs in public space reflect 'normalcy' in a community. The authors ask what restricting signs tell us about a society? In order to explore the system and variation in the ways dog signs manifest different norms and control, they compare two different data sets: dog signs in a Northern European town, Jyväskylä in Finland, and two Eastern European villages in Romania. They apply a qualitative methodology based on visual communication, geosemiotics and linguistic landscape studies. The focus of the article is on the resources of addressing and the visual semiotics of the image. The investigated communities seem to create a complementary distribution of what they regulate that is also displayed through their semiotics: the Jyväskylä examples are prohibitions for dogs 'being' while the Romanian cases consist of warnings or threats. Both prohibitions and warnings implicate the norms and normalities in the communities, showing where they stand in terms of a continuum between a 'dog as a pet' and a 'dog as a (co-)worker'. As images, the urban signs in Jyväskylä can be characterized as icons of a small collared pet, placed as a part of top-down communication in 'tight' public spaces. In contrast, the photographs of big dogs in the open and private Romanian village spaces refer to some specific guard dog, through which their owners communicate a benevolent warning or an intimidating threat.